COMPARING RATES OF TIBIAL SPINE FRACTURES TO ACL TEARS: A 7-YEAR TREND - Aoyama, Julien T (Orthop J Sports Med, 2020)
BACKGROUND: Sometimes referred to as the “pediatric” ACL injury, tibial spine fractures, although less commonly seen, are believed to share the same injury mechanism as anterior cruciate ligament (ACL) tears. And while incidence rates of pediatric ACL tears have been known to be increasing in recent years, to our knowledge, trends in incidence rates of tibial spine fractures (TSFs) in the pediatric population have not yet been reported in the literature. With sport specialization in children becoming a more commonly discussed topic, our goal was to report on the incidence rates of TSFs over a 7-year span at a single-center, and to compare rates of injury in these two conditions by sport and other patient characteristics. HYPOTHESIS/PURPOSE: TSF and ACL injuries are both on the rise but draw from different populations. METHODS: Retrospective comparison study of all patients presenting between 1/1/2010 and 1/1/17 with a TSF or an ACL tear at a single pediatric hospital. Medical records were queried for TSFs and ACL tears using ICD-10 and ICD-9 codes. Incidence rates over time were compared against one another. Incidence rates were further stratified based on sex, race, age, BMI, and sport/mechanism of injury, and bivariate analyses were performed to find significant differences between groups. RESULTS: 43 patients with a TSF and 947 patients with an ACL tear were identified. Graphical analysis showed an upward trend in the yearly incidence of both injuries, particularly in the last two years. TSF age ranged from 3 to 17 years with an average of 12.5 ± 2.8 years. ACL tear age ranged from 6 to 24 years with an average of 15.2 ± 2.3 years. Comparisons of sport, age, sex, and BMI were all found to have significant differences (p < .001 for all) between the two injuries. Race was not found to be significantly different between the two injuries. CONCLUSION: Our data supports the hypothesis that, similar to ACL tears, incidence rates of TSFs have been increasing in recent years. Injury during sport was found to be significantly different between the two injuries, with football being the most common sport for TSFs and soccer being the most common sport for ACL tears. ACL tears also draw from a slightly older age population (15.2 ± 2.3 years) than TSFs (12.5 ± 2.8 years), and TSFs are more commonly seen in males and those with lower BMI when compared to ACL tears.